Inflation Differentials in the EU : A Common (Factors) Approach with Implications for EU8 Euro Adoption Prospects. (IMF Working Papers; Working Paper, 2008)
This paper explores inflation determinants within the EU and implications for new members' euro adoption plans. Factor analysis partitions observed inflation in EU25 countries into common-origin and country-specific (idiosyncratic) components. Cross-country differences in common-origin inflation within the EU are found to depend on gaps in the initial price level, changes in the nominal effective exchange rate, the quality of institutions, and the economy's flexibility. Idiosyncratic inflation is generally small in magnitude. Nonetheless, the results show that country-specific shocks have systematically pushed down headline inflation, potentially influencing the assessment of compliance with the Maastricht inflation criterion.